2018
DOI: 10.1371/journal.pntd.0006649
|View full text |Cite
|
Sign up to set email alerts
|

Human rabies in Côte d'Ivoire 2014-2016: Results following reinforcements to rabies surveillance

Abstract: In Côte d’Ivoire, rabies is endemic and remains largely uncontrolled. The numbers of human exposures and rabies cases are unknown and are probably much higher than reported. Data on human rabies cases are collected by the National Institute of Public Health (NIPH) Anti-rabies Center in Abidjan through a network of 28 NIPH local units, which cover the population of the entire country. During 2014, the NIPH initiated a program to reinforce the human rabies surveillance system in those 28 NIPH local units, with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 20 publications
(40 reference statements)
3
26
1
1
Order By: Relevance
“…As found in other countries with endemic canine rabies [ 2 , 5 , 30 , 31 ], exposures were frequent in children, with over 40% in persons ≤ 15 years of age, and mostly involved dogs. The delay between animal exposure and medical consultation was short, which suggests good public awareness of the risk of rabies in the West region.…”
Section: Discussionsupporting
confidence: 63%
“…As found in other countries with endemic canine rabies [ 2 , 5 , 30 , 31 ], exposures were frequent in children, with over 40% in persons ≤ 15 years of age, and mostly involved dogs. The delay between animal exposure and medical consultation was short, which suggests good public awareness of the risk of rabies in the West region.…”
Section: Discussionsupporting
confidence: 63%
“…According to the report by the Center of Disease Control and Prevention in 2018, the overall incidence rate of animal bites had reached 216 per 100,000 population. Naghibi et al (2014) also reported this incidence rate by 203.4 per 100,000 population in Mazandaran Province, Iran, during 2007-2012. Besides, (Kassiri et al 2014a obtained an incidence rate of 282 per 100,000 individuals in the city of Ahvaz, Iran.…”
mentioning
confidence: 94%
“…Rabies is known as one of the most dangerous viral zoonotic diseases that can infect all mammals (Tiembré et al, 2018). Despite being preventable and given the existence of safe and effective vaccines, rabies has still remained a major health problem in numerous countries across the world (Kasem et al, 2019;Banyard et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Strengthening existing surveillance systems is an implementable action in Africa. In two accompanying reports, we describe efforts to strengthen regional surveillance programs in Cameroon and Ivory Coast, together with the results of over two years of surveillance [ 32 ][ 33 ]. The programs focused on engaging HCPs and veterinary authorities and improving their training in rabies surveillance, animal bite management, human rabies case diagnosis and management, as well as sampling techniques and sample management.…”
mentioning
confidence: 99%
“…This is nearly nine-fold more than the 57 exposures reported for the entire West Region in 2013 [ 34 ]. In Ivory Coast, 31,492 animal exposures and 50 suspected human cases were reported, and 32 of the 39 samples submitted for testing were laboratory confirmed [ 32 ]. By comparison, 26 cases of human rabies for the entire country were reported to the Ivory Coast national health ministry between 2001 and 2009, only four of which were sampled and then confirmed by postmortem laboratory analysis [ 35 ].…”
mentioning
confidence: 99%